A high plant density and the split application of chemical fertilizer increased the grain and protein content of cowpea (Vigna unguiculata) in Burkina Faso, west Africa - Ishikawa, H.; Batieno, Benoit Joseph; Fatokun, C.; Boukar, O. (MDPI, 2022)
In West Africa, cowpea (Vigna unguiculata) is an important source of protein for many people. To meet the protein demands, the cowpea yields per unit area and its seed protein content must be increased. We evaluated the effects of the planting density and topdressing (fertilisation) timing on the cowpea yield and its protein content. High density (HD: 40 × 40 cm) and super high density (SHD: 40 × 20 cm) plantings were the most efficient approaches for enhancing cowpea yields. Across different regions in Burkina Faso, under such approaches, the yield significantly increased by as much as 214.5%, with an average value of 88.9%. Fertilisation was not required to achieve the significant increases in cowpea production following dense planting. Although the yield increased, the seed weight per plant decreased with the increase in planting density. Applying topdressing when the plants started flowering increased the seed protein content significantly by up to 24.4%. Simple and robust technologies, such as high-density planting and topdressing, can be rapidly disseminated for increased cowpea yields and protein content improvement for Burkina Faso and for other countries.